Implementation of School Literacy Program in Improving Students' Reading Literacy Skills: A Qualitative Study at SD Negeri 2 Linggasari, Banyumas - Bamas Aprihadi Setiawan; Wanda Nugroho Yanuarto (UM Purwokerto Press, 2025)
Literacy is one of the problems faced by teachers at SD Negeri 2 Linggasari which of course has an impact on the learning process. This study aims to describe the impact of the implementation of the School Literacy Program in improving students' literacy skills at SD Negeri 2 Linggasari, Banyumas. The approach used is qualitative with data collection instruments in the form of questionnaires, interviews, observations, and documentation. Initial data shows that students' literacy skills in 2023 have decreased based on the results of the education report card. The subjects of the study included the principal, teachers, and students of SD Negeri 2 Linggasari who provided diverse perspectives on the effectiveness of the literacy program implemented. To overcome these problems, researchers implemented the School Literacy Movement through various literacy activities that are integrated into learning and the school environment. At the habituation stage, students are accustomed to reading or being read books other than textbooks, then discussion activities are carried out related to the books read. The development stage of literacy implementation is carried out with the aim of consistent student reading interest. At the learning stage, students are able to capture and re-explain the material given well. The results of the study showed that after the implementation of the literacy program, there was an increase in students' literacy skills in 2024. This finding indicates that the implementation of the School Literacy Program systematically and sustainably can have a positive impact on improving the literacy skills of elementary school students.